(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To apprehend the feelings and meanings about the sexuality of adult men with intestinal ostomies. Method: Thirty adult men with stomas participated of a qualitative, historical-analytical and comprehensive exploratory study. Data were obtained from interviews, followed by analysis anchored in thematic oral history, and data interpretation based on Ágnes Heller’s theory of feelings. Results: It has been shown that adult men with intestinal ostomies experience multiple feelings related to their sexuality, including impulsive, emotional, affective, and orienting feelings. Conclusion: The relevance of specialized and multidisciplinary care is highlighted to better meet the demands of sexual health, which is intertwined with psychic-social health, of men with stomas.